2022
DOI: 10.3389/fpsyg.2022.923558
|View full text |Cite
|
Sign up to set email alerts
|

Wearing the face mask affects our social attention over space

Abstract: Recent studies suggest that covering the face inhibits the recognition of identity and emotional expressions. However, it might also make the eyes more salient, since they are a reliable index to orient our social and spatial attention. This study investigates (1) whether the pervasive interaction with people with face masks fostered by the COVID-19 pandemic modulates the processing of spatial information essential to shift attention according to other’s eye-gaze direction (i.e., gaze-cueing effect: GCE), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 104 publications
3
11
3
Order By: Relevance
“…It is worth noting that, unlike previous studies showing independent coding of gaze direction and stimulus spatial location (e.g., Zorzi et al, 2003;Ricciardelli et al, 2007;Villani et al, 2021), we did not find additive effects of gaze direction and H-R compatibility, neither for RTs nor for error rates. Therefore, it seems that the stimulus spatial feature (i.e., the orientation of the object's handle) does not behave as the stimulus spatial location, hence, undermining the location coding account's assumption that the H-R compatibility effect is a kind of S-R compatibility effect (e.g., a Simon effect: Cho and Proctor, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that, unlike previous studies showing independent coding of gaze direction and stimulus spatial location (e.g., Zorzi et al, 2003;Ricciardelli et al, 2007;Villani et al, 2021), we did not find additive effects of gaze direction and H-R compatibility, neither for RTs nor for error rates. Therefore, it seems that the stimulus spatial feature (i.e., the orientation of the object's handle) does not behave as the stimulus spatial location, hence, undermining the location coding account's assumption that the H-R compatibility effect is a kind of S-R compatibility effect (e.g., a Simon effect: Cho and Proctor, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…If the two codes are independent, responses should be faster when the direction of the gaze is consistent with the spatial location of the response key and when the direction of the target's handle is consistent with the spatial location of the response key. This result would be in line with previous findings, showing independent coding of gaze direction and stimulus spatial location (e.g., Zorzi et al, 2003;Ricciardelli et al, 2007;Villani et al, 2021), and would speak in favor of the location coding account (e.g., Cho and Proctor, 2010) since it would assimilate the H-R compatibility effect to other spatial stimulus-response (S-R) compatibility effects, such as the Simon effect (Simon, 1990).…”
Section: The Present Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies suggested that covering the face inhibited the recognition of identity and emotional expressions. However, it may also make the eyes more prominent, since they are a reliable index to orient people’s social and spatial attention ( Villani et al, 2022 ). In addition, a questionnaire with a forced 4-choice-1-question format was used in this study, and the participants tended to choose the closest answer.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is here shown that spontaneous categorization processes are triggered, grouping individuals as a function of their mask-related behaviors. The implementation of preventive behaviors has become an integral part of people's daily lives, and much has already been done to highlight the possible effects on socio-cognitive processes 9,[52][53][54][55][56][57] . Although there is a widespread hope that we could soon overcome the Covid-19 pandemic, there is still uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%